HUBUNGAN KOMPETENSI PEDAGOGIK DENGAN KINERJA GURUDI KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Tandewi, Rizka; Novianti, Ria; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aim to determine the correlation between pedagogic competence and teacher performance in Pendalian IV Koto Distrct, Rokan Hulu Regency. The population of this study were all the teacher teachers in the Pendalian IV Koto, Rokan Hulu Regency, the total of the teachers were 31 people, then the sample of this research were 31 teachers. The method used in this study was the correlation to know the correlation between independent variable and dependent variable. The techniques of collecting data used in this research was quistioner in the form of a Likert scale . Data analysis techniques used in this research were a scale trial and analysis of statistical methods by SPSS for Windows Ver. 17. Based on the results of hypothesis testing, there is a significant positive correlation between pedagogic competence and teacher performance in Kecalian District of Pendalian IV Koto, Rokan Hulu Regency. it can be seen from the correlation coefficient value of 0.729 and significance level is 0.000 <0.05. The level of correlation between pedagogic competence and teacher performance is included in the strong category with the determinant coefficient value produced is KD = r2 x 100% = 0.7292 x 100% = 53.144%, it can be seen that Pedagogic Competence has an influence of 53.144%, on Teacher Performance.Key Words: Pedagogic Competence, Teacher Performance